CARE CR-Cardiovascular and cardiorespiratory Adaptations to Routine Exercise-based Cardiac Rehabilitation: a study protocol for a community-based controlled study with criterion methods. Issue 1 (27th January 2018) - Nichols, Simon; Nation, Fiona; Goodman, Toni; Clark, Andrew L; Carroll, Sean; Ingle, Lee
Abstract : Introduction: Cardiac rehabilitation (CR) reduces all-cause and cardiovascular mortality in patients with coronary heart disease (CHD). Much of this improvement has been attributed to the beneficial effects of structured exercise training. However, UK-based studies have not confirmed this. Improvements in survival and cardiovascular health are associated with concurrent improvements in cardiorespiratory fitness (CRF). It is therefore concerning that estimated CRF improvements resulting from UK-based CR are approximately one-third of those reported in international literature. Modest improvements in CRF suggest that UK CR exercise training programmes may require optimisation if long-term survival is to be improved. However, contemporary UK studies lack control data or use estimates of CRF change. Cardiovascular and cardiorespiratory Adaptations to Routine Exercise-based CR is a longitudinal, observational, controlled study designed to assess the short-term and long-term effect of CR on CRF, as well cardiovascular and cardiometabolic health. Methods and analysis: Patients will be recruited following referral to their local CR programme and will either participate in a routine, low-to-moderate intensity, 8-week (16 sessions) exercise-based CR programme or freely abstain from supervised exercise. Initial assessment will be conducted prior to exercise training, or approximately 2 weeks after referral to CR if exercise training is declined. Reassessment will coincide with completion of exercise training or 10 weeks after initial assessment for control participants. Participants will receive a final follow-up 12 months after recruitment. The primary outcome will be peak oxygen consumption determined using maximal cardiopulmonary exercise testing. Secondary outcomes will include changes in subclinical atherosclerosis (carotid intima–media thickness and plaque characteristics), body composition (dual X-ray absorptiometry) and cardiometabolic biomarkers. Ethics and dissemination: Ethical approval for this non-randomised controlled study has been obtained from the Humber Bridge NHS Research Ethics Committee—Yorkshire and the Humber on the 27th September 2013, (12/YH/0278). Results will be presented at national conferences and published in peer-reviewed journals.